Experiencing Time in Brian Cherney’s String Quartet No. 4 (1994) - Neidhöfer, Christoph (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
Brian Cherney’s Fourth String Quartet (1994), in one movement lasting half an hour, is striking for its formal coherence and diversity of materials. The work achieves large-scale cohesion not only through an intricate interplay of three simultaneously unfolding “main structures”—four attacca movements in one, on one level, seven sections forming certain temporal proportions, on another, and four cycles of “breathing rhythms” derived from the same proportions on a third level, as documented in the manuscript sources—but also through the continually fluctuating tension we experience throughout the movement between ontological and psychological time. Pierre Souvtchinsky’s notion of a “counterpoint” between “ontological time” (i.e., clock or real time) and a particular music’s inherent time shaped by “the material and technical means by which [the] music is expressed” is referenced to demonstrate how in Cherney’s quartet fixed proportions and slow, stable polyrhythms active in the background afford space for foreground activity that has its own sense of time. The article further explores the notion of time in a second, metaphorical dimension, as concerns intertextual allusions in the quartet.